Asia-Pacific currencies structure aftermath Tohoku earthquake - Atiany, Tareq A.M.; Sharif, Shamshuritawati (MAXWELL Science Publication, 2015)
This study investigates the aftermath of Tohoku earthquake to the structure of Asia-Pacific currencies.The M statistic and Minimum Spanning Tree (MST) are employed to study the stability of the covariance currencies structure and its causes, respectively.To filter the information from MST, we use a degree centrality measure. The results showed that the Tohoku earthquake that struck Japan on March 2011 had increased the volatility of currencies exchange and made currencies unstable. From the control chart, it shows that the currencies are not stable from Jan 2010 until Dec 2011.Based on sample data of Nov 2011, we can conclude that LKR and HKD are the unstable currencies among the others.